Efficiency Optimized Brushless DC Motor Drive based on Input Current Harmonic Elimination - Tridibesh Nag; Arijit Acharya; Debashis Chatterjee; Ashoke Kumar Ganguli; Arunava Chatterjee (Institute of Advanced Engineering and Science, 2015)
This paper describes efficiency improvement of a position sensorless brushless DC (BLDC) motor with improved PWM scheme for the inverter compared to existing ones. This is based on Selective Harmonic Elimination (SHE). The proposed method reduces total harmonic distortion (THD) from the input current and armature flux and thereby reducing the core losses. The effectiveness of the proposed scheme is demonstrated through simulation and experimental results.